Consensus for experimental design in electromyography (CEDE) project: Electrode selection matrix. (October 2019) - Besomi, Manuela; Hodges, Paul W.; Van Dieën, Jaap; Carson, Richard G.; Clancy, Edward A.; Disselhorst-Klug, Catherine; Holobar, Aleš; Hug, François; Kiernan, Matthew C.; Lowery, Madeleine; McGill, Kevin; Merletti, Roberto; et al.
Abstract: The Consensus for Experimental Design in Electromyography (CEDE) project is an international initiative which aims to guide decision-making in recording, analysis, and interpretation of electromyographic (EMG) data. The quality of the EMG recording, and validity of its interpretation depend on many characteristics of the recording set-up and analysis procedures. Different electrode types (i.e., surface and intramuscular) will influence the recorded signal and its interpretation. This report presents a matrix to consider the best electrode type selection for recording EMG, and the process undertaken to achieve consensus. Four electrode types were considered: (1) conventional surface electrode, (2) surface matrix or array electrode, (3) fine-wire electrode, and (4) needle electrode. General features, pros, and cons of each electrode type are presented first. This information is followed by recommendations for specific types of muscles, the information that can be estimated, the typical representativeness of the recording and the types of contractions for which the electrode is best suited. This matrix is intended to help researchers when selecting and reporting the electrode type in EMG studies.